2022
DOI: 10.1155/2022/5981020
|View full text |Cite
|
Sign up to set email alerts
|

Nasopalatine Duct Cyst with Impacted Inverted Mesiodens: A Rare Case Report and Literature Review

Abstract: Nasopalatine duct cyst (NPDC) is a non-odontogenic, developmental epithelial cyst that accounts for 1% of maxillary cysts. It often arises due to the spontaneous proliferation of the epithelial tissue remnants, although trauma, bacterial infection, and mucous retention may also trigger the proliferation. Owing to its slow-growing, asymptomatic nature, the cyst is often discovered as an accidental finding during routine clinical and radiographic examinations. However, the majority of cases present as a tiny, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Mesiodens can lead to severe complications, such as intraoral infections, cyst formation, delayed eruptions of permanent teeth causing significant discomfort, structural damage to the jaw, and prolonged treatment processes, which may involve surgical interventions and long-term management [1][2][3]. In rare instances, incisors may even erupt on the nasal floor, posing significant risks to oral health, such as severe infections, airway obstructions, and speech difficulties, necessitating immediate and specialized dental interventions, to prevent further complications and ensure proper oral function and aesthetics [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesiodens can lead to severe complications, such as intraoral infections, cyst formation, delayed eruptions of permanent teeth causing significant discomfort, structural damage to the jaw, and prolonged treatment processes, which may involve surgical interventions and long-term management [1][2][3]. In rare instances, incisors may even erupt on the nasal floor, posing significant risks to oral health, such as severe infections, airway obstructions, and speech difficulties, necessitating immediate and specialized dental interventions, to prevent further complications and ensure proper oral function and aesthetics [11].…”
Section: Discussionmentioning
confidence: 99%
“…It does not harm adjacent teeth (radiographically and clinically) [1,2]. It causes periapical infections like cysts [11].…”
Section: Indications Contraindicationsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 5 The exact pathophysiology of this lesion is still unknown, but it is believed that the remnants of the nasopalatine duct degenerate spontaneously into cysts. 6 While some researchers have proposed that NDCs originate from the spontaneous growth of epithelial tissue, the causes of these cysts are still unclear. 7 A central giant cell granuloma, a root cyst associated with the upper central incisors, a supernumerary tooth follicular cyst (usually mesiodens), a primordial cyst, a naso-alveolar cyst, osteitis with palatal fistulization, and bucco-nasal and/or bucco-sinusal communication are considered to be the differential diagnosis of NPCs.…”
Section: Introductionmentioning
confidence: 99%
“…These cysts originate from epithelial remnants in the nasopalatine duct [ 2 ]. The etiopathogenesis of nasopalatine duct cysts remains uncertain; however, some reports suggested that they arise due to the spontaneous proliferation of residual epithelial tissue due to several factors, such as mechanical trauma, bacterial infection, or mucous retention [ 3 , 4 ]. Cyst enucleation is a general treatment for nasopalatine cysts.…”
Section: Introductionmentioning
confidence: 99%